In vivo transplantation of stem cells with a genipin linked scaffold for tracheal construction. (July 2019) - Zhong, Yi; Yang, Wenlong; Yin Pan, Zi; Pan, Shu; Zhang, Si Quan; Hao Wang, Zhi; Gu, Sijia; Shi, Hongcan
To establish the procedures of genipin-linked scaffold for in situ tracheal reconstruction in a rabbit model, and to demonstrate whether stem cells can be further differentiated in the bioreactor in vivo. It will further provide an experimental and theoretical foundation for clinical application. Previously, in vitro evaluation proved the detergent–enzymatic method effectively removed stromal epithelial cells, and the number of nuclei was reduced significantly ( p  < 0.05). The content of type II collagen was not statistically reduced ( p  > 0.05). Plasmids with green fluorescence protein were transfected into 293T cells, and these cells subsequently synthesized lentivirus with green fluorescence protein that could infect other cells. After in vivo experiments, macroscopic specimen observation and hematoxylin and eosin staining comparison showed that the genipin cross-linked decellularized scaffold had low immunological rejection. Blood routine proved the progenitor cells (such as mononuclear cells) can be mobilized from the bone marrow by the growth factors, to allow their circulation into the peripheral blood. The immunohistochemistry of Type II collagen after surgery showed the expression level of bone marrow mesenchymal stem cells transplantated group was statistically higher than the autologous transplantated group ( p  < 0.05). The fluorescences of Bone marrow mononuclear cells (BMNCs) were traced after the specimens harvested. It successfully demonstrated that the procedures combining stem cells with the genipin cross-linked decellularized scaffold could apply to in situ airway construction. Compared to bone marrow mesenchymal stem cells, BMNCs can also be used to achieve chondrocyte differentiation; this procedure will avoid in vitro cell culture, shortening the time and economic costs.